Orphan nuclear receptor COUP‐TFII enhances myofibroblast glycolysis leading to kidney fibrosis - Li, Li (EMBO Rep, 2021)
Recent studies demonstrate that metabolic disturbance, such as augmented glycolysis, contributes to fibrosis. The molecular regulation of this metabolic perturbation in fibrosis, however, has been elusive. COUP‐TFII (also known as NR2F2) is an important regulator of glucose and lipid metabolism. Its contribution to organ fibrosis is undefined. Here, we found increased COUP‐TFII expression in myofibroblasts in human fibrotic kidneys, lungs, kidney organoids, and mouse kidneys after injury. Genetic ablation of COUP‐TFII in mice resulted in attenuation of injury‐induced kidney fibrosis. A non‐biased proteomic study revealed the suppression of fatty acid oxidation and the enhancement of glycolysis pathways in COUP‐TFII overexpressing fibroblasts. Overexpression of COUP‐TFII in fibroblasts also induced production of alpha‐smooth muscle actin (αSMA) and collagen 1. Knockout of COUP‐TFII decreased glycolysis and collagen 1 levels in fibroblasts. Chip‐qPCR revealed the binding of COUP‐TFII on the promoter of PGC1α. Overexpression of COUP‐TFII reduced the cellular level of PGC1α. Targeting COUP‐TFII serves as a novel treatment approach for mitigating fibrosis in chronic kidney disease and potentially fibrosis in other organs.